Protocatechuic Aldehyde Alleviates d-Galactose–Induced Cardiomyocyte Senescence by Regulating the TCF3/ATG5 Axis. Issue 3 (March 2023) - Wang, Pengjun; Zhang, Qingxiang
Abstract: Cardiomyocyte senescence is an independent risk factor for cardiovascular diseases. Protocatechuic aldehyde (PCA) is a natural chemical in the Chinese medicinal herb Salvia miltiorrhiza . PCA could protect against oxidative stress and inflammation in the cardiovascular system. In present study, we treated H9C2 cells with d -galactose to establish an in vitro model of cardiomyocyte senescence and investigated the role and underlying mechanisms of PCA in myocardial cell senescence. It was found that d -galactose induced transcription factor 3 (TCF3) expression and decreased autophagy-related genes 5 (ATG5) expression. Meanwhile, inflammation and senescence were exacerbated by d -galactose. TCF3 transcriptionally inhibited ATG5 expression. TCF3 knockdown abolished the effects of d -galactose on H9C2 by activating ATG5-mediated autophagy. PCA hindered TCF3 and inflammation to alleviate the d -galactose–induced senescence of H9C2 cells in a dose-dependent manner. Whereas, the anti-inflammation and anti-senescence effects of PCA were reversed by TCF3 knockdown. Furthermore, absence of ATG5 partially eliminated the impacts of PCA on H9C2 cells treated with d -galactose. Conclusively, PCA alleviated d -galactose–induced senescence by downregulating TCF3, promoting ATG5-mediated autophagy, and inhibiting inflammation in H9C2 cells. These results elucidated the potential mechanism by which PCA alleviated cardiomyocyte senescence and enabled its application in treating cardiomyocyte senescence.